RENAISSANCE – REBIRTH: SOME REMARKS ABOUT THE HUMANISTIC INTERPRETATION OF HISTORY - Kablitz, Andreas (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 2001)
The author works towards a historical understanding of humanism through his analysis of the notion of rebirth which was a key concept, but under different guise, both in the self-interpretation of the sixteenth century as well as in the appearance, during the nineteenth century, of the term "Renaissance" when it was first used to describe a historical period. However, the contexts of Vasari’s use of the word rinascita and later of Michelet’s use of the word Renaissance differ greatly. Whereas in Vasari, rebirth is meant to reinterpret the relationship of art to nature against nominalism’s views that there are pre-ordained possibilities, in Michelet rebirth is meant to refer to the development of empirical studies of nature and the retrieval of the Greek and Latin program of self-constitution for mankind through the work of reason. Hence, the Middle Ages, and scholasticism especially, are blamed for their suppression of nature. The loss of the importance of art in Michelet's conception of the Renaissance follows logically from the interpretation of this period as a re-establishment of truth. On the contrary, if art is of crucial importance in Vasari's conception of rinascita, it is because art as creation opens all possibilities and, thus, is part of an effort towards perfection.